Determinant Football Elements for Euro16 Match Results - Rocha-Lima, Eric Matheus; Wallan Tertuliano, Ivan; Norberto Fischer, Carlos (Journal of Sustainable Competitive Intelligence, 2023)
Purpose: The current article aimed to verify patterns that could explain match results of the Euro Cup 2016, using as references the following match performance indicators: finishing, ball possession, passing, crosses and defensive actions. Methodology/approach: The necessary information about the matches was collected from the Dailymail’s website. The Weka (Waikato Environment for Knowledge Analysis) program was adopted to help in the analyses of these data. Originality/Relevance: Football matches components have been analysed in order to understand the behavior of the teams in the competitive scenario of this sport. Key findings: The results show that the more accurate shots a national squad takes in their games, the more chances they got to win, instead of using a game plan based on crossing movements. Ball possession, on its turn, can be a good indicator or a bad one to win matches, when associated to a high number of crosses. Moreover, the alternative of long passes seems to be relevant only when the opponent makes more shots from outside the area or get more blocked shots. Complementarily, defensive actions focused on successful tackles and more interceptions appear as a positive aspect for getting the triumph, considering only the total number of tackles. The accuracy of kicks and defensive actions were relevant to the success of the teams in the competition, suggesting that the improvement of actions related to these two indicators should help national teams to improve their own strengths, in order to maximize their chances of winning matches. Theoretical/methodological contributions: Collecting a large volume of football data from a website and using the Weka program have helped not only to speed up and facilitate the analyses but also should have been important in order not to lose any relation that could be relevant inside the studied scenario.